2017
DOI: 10.1002/advs.201700080
|View full text |Cite
|
Sign up to set email alerts
|

Local Bonding Influence on the Band Edge and Band Gap Formation in Quaternary Chalcopyrites

Abstract: Quaternary chalcopyrites have shown to exhibit tunable band gaps with changing anion composition. Inspired by these observations, the underlying structural and electronic considerations are investigated using a combination of experimentally obtained structural data, molecular orbital considerations, and density functional theory. Within the solid solution Cu2ZnGeS4− xSex, the anion bond alteration parameter changes, showing larger bond lengths for metal–selenium than for metal–sulfur bonds. The changing bondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 59 publications
(110 reference statements)
1
18
0
Order By: Relevance
“…The band gap of the sprayed films is calculated using Tauc's relation using the following equation: (normalαnormalhnormalv)2=Btrue(hvEgtrue) where α , B , and Eg are the absorption coefficient, proportionality constant, and optical band gap; respectively, the absorption coefficient is calculated by the following equation: α=2.303At where A and t are the absorbance and thickness, respectively, Figure shows the band gap of pure and Ba‐doped Mn 3 O 4 thin films, the values fairly agree with the work reported in literature . It is found that band gap varies as Ba concentration increases reaching a minimum value 2.85 eV in Mn 3 O 4 :Ba1% thin films, the reduction in band gap may be due to the increase in RMS roughness and crystallite size as reported earlier, it is also observed band gap decreases with the increase in unit cell volume as well as bond lengths of (Mn 2+ O) and (Mn 3+ O) in tetrahedral and octahedral sites; respectively (see Table ) as Ba concentration increases, this behavior agrees with the findings reported in literature …”
Section: Resultssupporting
confidence: 54%
“…The band gap of the sprayed films is calculated using Tauc's relation using the following equation: (normalαnormalhnormalv)2=Btrue(hvEgtrue) where α , B , and Eg are the absorption coefficient, proportionality constant, and optical band gap; respectively, the absorption coefficient is calculated by the following equation: α=2.303At where A and t are the absorbance and thickness, respectively, Figure shows the band gap of pure and Ba‐doped Mn 3 O 4 thin films, the values fairly agree with the work reported in literature . It is found that band gap varies as Ba concentration increases reaching a minimum value 2.85 eV in Mn 3 O 4 :Ba1% thin films, the reduction in band gap may be due to the increase in RMS roughness and crystallite size as reported earlier, it is also observed band gap decreases with the increase in unit cell volume as well as bond lengths of (Mn 2+ O) and (Mn 3+ O) in tetrahedral and octahedral sites; respectively (see Table ) as Ba concentration increases, this behavior agrees with the findings reported in literature …”
Section: Resultssupporting
confidence: 54%
“…3 and 4b), as was the cases in the solid solutions Cu 2 -ZnGeS 4Àx Se x (ref. [39][40][41] or Cu 2Àx Se. 42 The existence of the repelling force upon Ag incorporation can be supported by the analyzed Raman spectra (shown in Fig.…”
Section: Te Performancementioning
confidence: 99%
“…The panel (c‐g) in Figure represent the plots of ( A.hν ) 2 versus photon energy ( hν ) for different x values. The widening of the bandgap can be ascribed to the reduction of p‐d hybridization caused by weakened CuS bond interaction . The calculated E g values are smaller than those experimentally determined (1.05–1.51 eV) as a result of GGA problem, while the latter ones are comparable to 1.21 eV from the synthesis in solvent .…”
Section: Resultsmentioning
confidence: 59%
“…Inspired by the influence of bonding interactions on the band structures and phonon transport property observed in quaternary Cu 2 ZnGeQ 4 (Q = S, Se), we take underlying crystal and electronic structure regulations in Cu 3 SnS 4 into consideration. Due to the small difference of radius and electronegativity between Sn 4+ (0.55 Å, 1.96) and Sb 5+ (0.565 Å, 2.05), Sb is presumably energetically favorable to Sn site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation